The Effectiveness of ELSA Speak in Facilitating Students’ Pronunciation in Storytelling - Hesa nizar (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
Pronunciation is an essential component of oral communication, especially in English as Foreign Language (EFL) storytelling. However, many junior high school students face difficulties with clarity, intonation, and fluency. This study aimed to investigate the effectiveness of the ELSA Speak application in improving students’ English pronunciation in storytelling. A quantitative quasi-experimental design was applied, involving 71 eighth-grade students of SMPN 1 Kunjang, divided into two groups: Class 8F as the experimental group using ELSA Speak and Class 8G as the control group taught through conventional methods. Both pre-test and post-test were administered to measure pronunciation performance, and the data were analyzed using Analysis of Covariance (ANCOVA). The results revealed that students in the experimental group achieved significantly better pronunciation improvement compared to the control group. The ANCOVA analysis confirmed a significant effect of ELSA Speak on students’ pronunciation (p < .001). The application’s real-time and individualized feedback mechanism enabled students to detect and correct pronunciation errors instantly, which fostered autonomous learning and consistent practice. Unlike delayed teacher correction, ELSA Speak provided immediate reinforcement that accelerated accuracy and fluency development. These findings highlight the effectiveness of incorporating AI-based applications into English language learning, particularly for enhancing pronunciation in storytelling contexts.